High-pressure processing (HPP) impacts on Indian mackerel meat: insights into quality attributes, β-parvalbumin antigenicity, and proteomic changes - Enchangan, Marcella Meia Gary; Seman, Muhammad Syamil; Al-Obaidi, Jameel R.; Zakaria, Atiqah Farah; Abdull Razis, Ahmad Faizal; Saari, Nazamid; Harith, Hanis Hazeera; Jambari, Nuzul Noorahya (Elsevier B.V., 2025)
High-pressure processing (HPP) is a non-thermal method that uses high hydrostatic pressure on food products to improve quality and shelf life. However, it can cause structural changes in proteins that alter food characteristics. This study investigated the effects of high-pressure processing (HPP) at 200, 400, and 600 MPa for 5 or 20 min on the quality, protein profiles, and antigenicity of β-parvalbumin, a major fish allergen, in Indian mackerel fillets. It also examined the in vitro digestibility of total protein and β-parvalbumin after HPP treatments. Protein profiles of the 600 MPa 5-minute treated and untreated fillets were analysed using 2D-PAGE, and proteins with significant changes were identified via MALDI-TOF/TOF MS. Results revealed that HPP at 400 and 600 MPa significantly increased fillet hardness and whiteness while reducing soluble protein content. Though β-parvalbumin was present in all treated samples, its levels decreased after digestion, becoming undetectable after 15 min. Specific proteins, including β-parvalbumin, actin, and ATP synthase, were significantly altered in the 600 MPa-treated fillets. HPP surpassing 600 MPa enhanced β-parvalbumin digestibility and reduced its antigenicity. These findings highlighted the delicate balance required in optimising HPP for improved digestibility and minimising the antigenicity of β-parvalbumin in Indian mackerel without compromising its quality.